Arthroscopic Margin Convergence Repair Without Suture Anchors Improves Clinical Outcomes for Full- and Partial-Thickness Rotator Cuff Tears - S. Ali Ghasemi, M.D; Benjamin Murray, D.O; Adam Lencer, D.O; Emily Schueppert, D.O; James Raphael, M.D; Craig Morgan, M.D; Arthur Bartolozzi, M.D (Elsevier, 2024)
Purpose: To evaluate the clinical outcome scores of an arthroscopic margin convergence technique without the use of suture anchors to repair different types of rotator cuff tears and to determine whether the type or extent of the tear has an effect on clinical outcome scores after this procedure. Methods: Patients receiving arthroscopic margin convergence repair without suture anchors for rotator cuff tears from 2013 to 2018 were retrospectively analyzed. Arthroscopically determined partial- or full-thickness rotator cuff tears with a minimum follow-up period of 20 months were included. Outcomes were assessed using the American Shoulder and Elbow Surgeons (ASES) shoulder score; University of California, Los Angeles (UCLA) shoulder score; and visual analog scale (VAS) score. A 2-tailed distribution paired t test was used to determine statistical significance (P < .05) between preoperative scores and scores at final follow-up. Correlation tests and linear regression analysis were used to determine the correlation between various clinical variables and outcomes. A cohort-specific minimal clinically important difference analysis was performed for each outcome score, calculated as one-half of the standard deviation of the delta score. Results: A total of 38 patients were included for analysis: 12 with partial-thickness tears and 26 with full-thickness tears. The mean postoperative follow-up period was 33.9 months (range, 22.2-94.5 months), with a minimum follow-up period of 22 months. The mean age of the patients was 62 ± 15.1 years. The minimal clinically important difference values for the ASES, UCLA, and VAS scores were 9.68, 2.92, and 1.13, respectively. There were significant improvements in the ASES (from 29.3 ± 18.3 preoperatively to 93.7 ± 8.3 postoperatively, P = .001), UCLA (from 14.3 ± 6.2 to 32.8 ± 2.6, P = .001), and VAS (from 7.37 ± 1.8 to 0.63 ± 1.02, P = .001) clinical outcome scores. However, patients with either Patte stage 3 retraction (P = .033 for ASES score and P = .020 for UCLA score) or U-shaped tears (P = .047 for ASES score and P = .050 for UCLA score) had significantly lower clinical outcome scores than patients with less severe retraction or differently shaped tears. Conclusions: The arthroscopic margin convergence technique without the use of suture anchors may be a suitable option in patients with partial- or full-thickness rotator cuff tears. Level of Evidence: Level IV, therapeutic case series.